New-insight UVB Treatment for Psoriasis Vulgaris in Vietnamese Patients - Phuong Pham Thi Minh; Trang Trinh Minh; Phuong Hoang Thi; Giang Quach Thi Ha; Tra Bui Thi; Michael Tirant; Doanh Le Huu (Indian Journal of Dermatology)
Background: Narrowband UVB (NBUVB) has recently been used in Vietnam for the treatment of psoriasis. However, there are no data on Vietnamese patients to adopt a uniform national protocol. Objectives: This study aimed to establish an optimal NBUVB therapy for the treatment of psoriasis in Vietnamese patients. Materials and Methods: One hundred and twenty-two patients with psoriasis vulgaris were included. They were randomly allocated to two groups: the percentage dose (group 1, 62 patients) and the fixed dose (group 2, 60 patients). In group 1, the starting dose was 50% of the minimal erythema dose (MED) and the 10% increment dose adjusted in the next sessions. In group 2, the starting dose was based on Fitzpatrick skin types (fixed dose). Psoriasis area and severity index (PASI) was used to evaluate efficacy. Results: More than 68% of the patients get PASI75 at session 36. Group 2 had significantly fewer sessions (20 ± 5 vs 25 ± 7, P- value = 0.0004) and lower cumulative dose than group 1 (14.1 ± 4.3 J/cm2 vs 18.0 ± 8.0 J/cm2, P- value = 0.0075) to achieve PASI75. Adverse effects were more common in group 2 than group 1, including burning sensation/erythema (43.33% vs 14.52%, P- value = 0.0009) and pruritus (75.00% vs 22.58%, P- value <0.0001). Conclusion: NBUVB therapy was safe and effective for Vietnamese psoriasis patients. Fixed doses produced a quicker clinical response with fewer sessions and lower cumulative doses. Adverse effects were mild in both groups and less noted for the MED-based dose. For the recommendation, a fixed dose should be applied for patients who have less concern about side effects, while a MED-based dose can be suitable for patients having conditions related to light sensitivity.